Ab initio study of iron adatom-vacancies in armchair graphene nanoribbons. (August 2018) - Benchallal, L.; Haffad, S.; Boubenider, F.; Lamiri, L.; Zitoune, H.; Kahouadji, B.; Samah, M.
Abstract: Using density functional theory, the structural stabilities, electronic and magnetic properties of Fen (n = 1–3) clusters absorbed on defected armchair graphene nanoribbons are systematically investigated. We found that such systems have high stabilities and large magnetic moments. From n = 3, the binding energies are very important compared with those of less number n. This can be explained by the fact that a triangularization phenomenon between iron atoms and also more bonds with neighboring carbon atoms. Fe3 -3V-AGNR exhibits a half-metal behavior with 61% spin polarization. Highlights: Fen /AGNR systems have high stabilities and large magnetic moments. Fen /AGNR may be halfmetal with 61% spin polarization (n = 3) or semiconductor (n = 1 and 2). These systems are promising materials for designing new nanodevices.